Kriteria Itikad Tidak Baik Bank Dalam Pelaksanaan Lelang Atas Objek Hak Tanggungan - Nabilah Nurmasitha (International Forum of Researchers and Lecturers, 2024)
From traditional trading practices to today's global financial system, credit agreements have played an important role in the formation of the world economy. Good faith can often be said to be a high norm in civil law, especially in contracts, because objective good faith refers to a normative concept related to moral standards in carrying out legal actions, especially in carrying out auctions. Bad faith is a contario of the definition of good faith, namely that good faith will be the background for someone to act against the law which results in harm to another party. Bad faith has not been clearly regulated in any statutory regulations, so determining whether someone is acting in bad faith is not easy considering that there are no provisions related to bad faith in statutory provisions, including BW. This research aims to analyze the basic determinants of bad faith in the implementation of mortgage rights execution auctions by banks based on credit agreements and the legal consequences for banks who act in bad faith in implementing mortgage rights auctions. The research method used in the research is normative legal research using a statutory approach, case approach and conceptual approach. This research uses legal materials sourced from primary legal materials and secondary legal materials which are then collected through literature study, analyzed using qualitative methods. The results of the research are that the basis for determining the existence of bad faith can be seen from actions that violate the law which are not based on the principle of caution or are not careful in carrying out their duties. Therefore, as a legal consequence of bad faith, you can file a lawsuit for cancellation of the auction which causes the auction to be canceled to the Local District Court.